International handbook of research on children's literacy, learning and culture - Hall, Kathy, 1952-; Cremin, Teresa; Comber, Barbara; Moll, C. Luis. (Chichester, West Sussex : Wiley-Blackwell, 2013)
'The International Handbook of Research in Children's Literacy, Learning and Culture presents a careful distillation of the current research in the field of primary years literacy studies'--
Includes bibliographical references and index.
Keywords: Language arts (Primary) -- Handbooks, manuals, etc; Reading (Primary) -- Handbooks, manuals, etc; Literacy -- Handbooks, manuals, etc; Multicultural education